Analysis of the Effect of Financial Performance Before and After the Implementation of the Harmonization of Tax Regulations - Negara, Noor Adi Sukma; Handrito, Radityo Putro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to analyze the effects of financial performance based on the aspects of liquidity (current ratio), activity (receivable turnover and inventory turnover), solvability (debt-to-equity ratio and return on equity), and profitability (operating profit margin and net profit margin) before and after the application of Tax Regulation Harmonization Law (UU HPP) in cigarette subsector companies listed on the IDX. This quantitative study uses secondary data in the form of the financial statements of five companies from 2021 to 2022 published in the Indonesia Stock Exchange. The results of the statistical descriptive analysis performed in IBM SPSS version 24 indicate that the aspects of liquidity (current ratio), activity (receivable turnover and inventory turnover), solvability (debt-to-equity ratio and return on equity), and profitability (operating profit margin and net profit margin) have no significant impact after the application of the Tax Regulation Harmonization Law (UU HPP).